Water-based adhesive and preparation method thereof
By building a multi-level collaborative system of dynamic supramolecular networks and covalent crosslinking networks, combined with environmental response units, the problem of traditional water-based adhesives being difficult to take into account water resistance, toughness and functionality is solved, and a significant improvement in water resistance, toughness and functionality is achieved.
Patent Information
- Application Number
- CN202510956124.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2025-08-26
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional water-based adhesives are difficult to take into account both water resistance, toughness and functionality. Existing research often sacrifices other properties when optimizing a certain performance through a single means.
By constructing a dynamic supramolecular network and a covalent crosslinking network, combined with environmental response units, N-(3,4-dihydroxyphenylethyl) methacrylamide, phenylboric acid functionalized polyethylene glycol, polyethyleneimine-dopamine copolymer, sulfobetaine methacrylate, epoxidized cashewol-polycaprolactone copolymer, methyltetrahydrophthalic anhydride, sulfobetaine/boron nitride hybrid filler, acrylic boric acid core-shell hyperbranched polyester and other components are used to form a multi-stage synergistic system, using dynamic boric acid ester bonds, covalent ester bonds and hydrophobic structures to improve water resistance and toughness, and realize functionality through catechol groups and hydrogen bonds.
The water resistance, toughness and functionality of water-based adhesives have been improved, water resistance is improved by more than 50%, toughness is increased by 20%, and functional stability is enhanced, solving the problems of traditional water-based adhesives losing stickiness and unstable performance when encountering water.
Smart Images

Figure CN120536059A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to a water-based adhesive and a preparation method thereof. Background Art
[0002] Water-based adhesives are environmentally friendly adhesives that use water as a dispersion medium or solvent. They form a bonding system by dissolving or dispersing natural polymers (such as starch) or synthetic polymers (such as polyurethane and acrylates). Their core advantage lies in their environmental friendliness. Compared to traditional solvent-based adhesives, they contain significantly lower levels of volatile organic compounds (VOCs). They are non-toxic, non-flammable, and easy to clean up residual adhesive. Their application areas include packaging, automotive, textiles, construction, furniture, and other industries, playing a significant role in improving product environmental performance and operational safety.
[0003] Traditional water-based adhesives face the core challenge of balancing water resistance, toughness, and functionality in practical applications. Existing research often optimizes a single property through a single approach, such as increasing crosslink density to improve water resistance at the expense of toughness, or introducing flexible segments to improve toughness but degrade water resistance. Furthermore, the introduction of functional groups (such as catechol and boric acid) often leads to unstable material properties due to poor interfacial compatibility and uneven dispersion, preventing the synergistic improvement of water resistance, toughness, and functionality. Therefore, balancing water resistance, toughness, and functionality in water-based adhesives is a pressing technical challenge. Summary of the Invention
[0004] The present application provides a water-based adhesive and a preparation method thereof to solve the following technical problem: how to balance the water resistance, toughness and functionality of the water-based adhesive.
[0005] In the first aspect, the present application provides a water-based adhesive, which is composed of the following chemical components, in parts by mass: 3.5 to 5.0 parts of N-(3,4-dihydroxyphenylethyl)methacrylamide, 2.5 to 3.5 parts of phenylboronic acid functionalized polyethylene glycol, 1.2 to 2.0 parts of polyethyleneimine-dopamine copolymer, 3.0 to 4.0 parts of sulfobetaine methacrylate, 27.0 to 32.0 parts of epoxidized cardanol-polycaprolactone copolymer, 7.0 to 10.0 parts of methyltetrahydrophthalic anhydride, 4.5 to 6.5 parts of sulfobetaine / boron nitride hybrid filler, 6.0 to 8.0 parts of acrylic acid boric acid core-shell hyperbranched polyester, 0.3 to 0.5 parts of photoinitiator, 0.3 to 0.5 parts of leveling agent, and 30.0 to 35.0 parts of deionized water.
[0006] Optionally, the number average molecular weight of the phenylboronic acid functionalized polyethylene glycol is 1800 to 2200, and the phenylboronic acid grafting rate is 85 to 95%; and / or,
[0007] In the polyethyleneimine-dopamine copolymer, the branching degree of polyethyleneimine is 0.35-0.45, and the grafting amount of dopamine is 1.8-2.2 mmol / g; and / or,
[0008] The epoxy value of the epoxidized cardanol-polycaprolactone copolymer is 0.25-0.35 eq / 100 g, and the molecular weight of the polycaprolactone segment is 2000-3000.
[0009] Optionally, the core of the acrylic acid boronic acid core-shell hyperbranched polyester is a hyperbranched polyester, the shell is acrylic acid boronic acid, the generation number of the hyperbranched polyester is 3.0-4.0, and the functionality of the acrylic acid boronic acid is 2.8-3.2 mmol / g.
[0010] Optionally, in the sulfobetaine / boron nitride hybrid filler, the boron nitride is hexagonal boron nitride, and the sulfobetaine methacrylate is modified on the surface of the hexagonal boron nitride, with the modification amount being 20-25% of the mass of the hexagonal boron nitride.
[0011] Optionally, the photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone; and / or,
[0012] The leveling agent is polyether modified siloxane.
[0013] In a second aspect, the present application provides a method for preparing the water-based adhesive according to any one of the first aspects, the method comprising the following steps:
[0014] S1, mixing N-(3,4-dihydroxyphenylethyl) methacrylamide, phenylboronic acid functionalized polyethylene glycol, polyethyleneimine-dopamine copolymer, sulfobetaine methacrylate and deionized water, and adjusting the pH to 6.8-7.2 to obtain a first mixed solution;
[0015] S2, adding a photoinitiator to the first mixed solution to perform ultraviolet light curing to obtain a second mixed solution;
[0016] S3, plasma-treating the sulfobetaine / boron nitride hybrid filler to obtain a pretreated filler;
[0017] S4, adding epoxidized cardanol-polycaprolactone copolymer, methyltetrahydrophthalic anhydride and acrylic acid boric acid core-shell hyperbranched polyester to the second mixed solution, then performing stepwise thermal curing, and adding pretreated filler during the stepwise thermal curing process to obtain a third mixed solution;
[0018] S5. Add a leveling agent to the third mixed liquid cooled to room temperature to obtain a water-based adhesive.
[0019] Optionally, the wavelength of the UV curing is 365 nm, the irradiation time is 5 to 10 min, and the light intensity is 50 to 70 mW / cm 2 and / or,
[0020] The working gas for the plasma treatment is an argon / oxygen mixed gas with a volume ratio of 4:1, the power is 100 W, and the treatment time is 2 to 5 minutes.
[0021] Optionally, step S4 includes:
[0022] S401, adding epoxidized cardanol-polycaprolactone copolymer, methyltetrahydrophthalic anhydride and acrylic acid boric acid core-shell hyperbranched polyester to the second mixed solution to obtain a first epoxy mixture;
[0023] S402, heating the first epoxy mixture to 70° C. and keeping the temperature for 2 hours to obtain a second epoxy mixture;
[0024] S403, continuing to heat the second epoxy mixture from 70° C. to 90° C. and keeping the temperature for 1 hour, adding the pretreated filler during the 1 hour of keeping the temperature, to obtain a third epoxy mixture;
[0025] S404, continuing to heat the third epoxy mixture from 90° C. to 120° C. and keeping the temperature for 30 minutes to obtain a third mixed solution.
[0026] Optionally, the preparation method of the sulfobetaine / boron nitride hybrid filler includes:
[0027] dispersing hexagonal boron nitride powder in concentrated nitric acid to perform surface hydroxylation on the hexagonal boron nitride to obtain activated hexagonal boron nitride;
[0028] The activated hexagonal boron nitride is dispersed in deionized water, and then sulfobetaine methacrylate monomer and azobisisobutylamidine hydrochloride are added, and a graft polymerization reaction is carried out under nitrogen protection to covalently bond the sulfobetaine methacrylate to the surface of the hexagonal boron nitride to obtain the sulfobetaine / boron nitride hybrid filler;
[0029] Wherein, the mass of the sulfobetaine methacrylate monomer is 20% to 25% of the mass of the hexagonal boron nitride;
[0030] The mass of the azobisisobutylamidine hydrochloride is 1% to 2% of the mass of the sulfobetaine methacrylate monomer;
[0031] The graft polymerization reaction temperature is 60-70° C. and the reaction time is 8-12 hours.
[0032] Optionally, the preparation method of the acrylic acid boric acid core-shell hyperbranched polyester includes:
[0033] Pentaerythritol, malonic anhydride and p-toluenesulfonic acid are dissolved in xylene solvent to carry out polycondensation reaction to obtain hyperbranched polyester;
[0034] The hyperbranched polyester is dissolved in tetrahydrofuran, and then acrylic acid boronic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are added to introduce acrylic acid boronic acid groups into the terminal hydroxyl groups of the hyperbranched polyester to obtain the acrylic acid boronic acid core-shell hyperbranched polyester;
[0035] Wherein, the molar ratio of the pentaerythritol to the malonic anhydride is 1:(3-4);
[0036] The mass of the p-toluenesulfonic acid is 0.5 to 1.5% of the total mass of the pentaerythritol and the malonic anhydride;
[0037] The polycondensation reaction temperature is 140-160°C and the time is 4-6 hours;
[0038] The functionality of the acrylic acid boronic acid is 2.8 to 3.2 mmol / g, and the molar ratio of the acrylic acid boronic acid to the hydroxyl group of the hyperbranched polyester is (1 to 1.2):1;
[0039] The molar ratio of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to the acrylic acid boric acid is (1.5-2.0):1;
[0040] The thickness of the acrylic acid boric acid shell layer is 5 to 10 nm.
[0041] The above technical solution provided by this application has the following advantages compared with the existing technology:
[0042] The present application provides a water-based adhesive and a preparation method thereof. The water-based adhesive is composed of the following chemical components: 3.5-5.0 parts of N-(3,4-dihydroxyphenylethyl)methacrylamide, 2.5-3.5 parts of phenylboronic acid functionalized polyethylene glycol, 1.2-2.0 parts of polyethyleneimine-dopamine copolymer, 3.0-4.0 parts of sulfobetaine methacrylate, 27.0-32.0 parts of epoxidized cardanol-polycaprolactone copolymer, 7.0-10.0 parts of methyltetrahydrophthalic anhydride, 4.5-6.5 parts of sulfobetaine / boron nitride hybrid filler, 6.0-8.0 parts of acrylic acid boric acid core-shell hyperbranched polyester, 0.3-0.5 parts of photoinitiator, 0.3-0.5 parts of leveling agent, and 30.0-35.0 parts of deionized water.
[0043] First, the long alkyl chains of cardanol in the epoxidized cardanol-polycaprolactone copolymer form a hydrophobic barrier, blocking the permeation path of water molecules and reducing water absorption. At the same time, the stacking of the hexagonal boron nitride layered structure of the sulfobetaine / boron nitride hybrid filler further hinders water diffusion and assists in improving water resistance. In addition, methyltetrahydrophthalic anhydride and epoxidized cardanol undergo ring-opening polymerization to form a hydrolysis-resistant ester bond, and the hydrolysis rate in a neutral environment is more than 50% lower than that of the traditional epoxy-amine system. The acrylic acid boric acid core-shell hyperbranched polyester is anchored in the network through covalent ester bonds to avoid water seepage in the pores caused by filler shedding. The water resistance of the water-based adhesive is improved by the dual protection of the hydrophobic structure and the hydrolysis-resistant network;
[0044] Secondly, the catechol of N-(3,4-dihydroxyphenylethyl) methacrylamide and the boronic acid group of phenylboronic acid functionalized polyethylene glycol form a dynamic borate ester bond. Under external force, the bond can reversibly break and reorganize, dissipating energy and improving the elongation at break. At the same time, the primary amine of the polyethyleneimine-dopamine copolymer forms a boron-nitrogen bond with the borate ester, which enhances the toughness of the network while preventing excessive slippage of the flexible chain segment. In addition, the polyethylene glycol and polycaprolactone segments provide the flexible chain segment with mobility, forming a microphase separation structure with the rigid cardanol-epoxy segment. The rigid domain resists external forces, and the flexible domain consumes energy through chain segment movement, achieving "high strength + high toughness". The toughness of the water-based adhesive is improved by the synergistic effect of dynamic bond energy consumption and flexible chain segments;
[0045] Thirdly, the catechol groups coordinate with metals through hydrogen bonds to penetrate the water film, forming strong adhesion at wet interfaces and resolving the "wet-detack" problem of traditional adhesives. The pH-responsive borate ester bond (acid-stable, alkaline-dissociated) formed by phenylboronic acid and catechol enables self-healing. The zwitterionic structure of sulfobetaine methacrylate inhibits bacterial adhesion while reducing surface energy, promoting uniform dispersion of components and avoiding performance degradation caused by phase separation. The acrylic boric acid core-shell hyperbranched polyester is dually anchored through covalent ester and BO bonds, ensuring long-term exposure of functional components (such as boric acid groups and catechol), maintaining wet adhesion and self-healing properties. Through environmentally responsive units and interface regulation mechanisms, the functionality of the water-based adhesive is enhanced.
[0046] Therefore, the present application takes into account the water resistance, toughness and functionality of the water-based adhesive by rationally designing the chemical composition of the water-based adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0048] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0049] Figure 1 A schematic flow chart of a method for preparing a water-based adhesive provided in an embodiment of the present application. DETAILED DESCRIPTION
[0050] To make the purpose, technical solutions, and advantages of the embodiments of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.
[0051] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0052] The present application provides a water-based adhesive, which is composed of the following chemical components, in parts by mass: 3.5-5.0 parts of N-(3,4-dihydroxyphenylethyl)methacrylamide, 2.5-3.5 parts of phenylboronic acid functionalized polyethylene glycol, 1.2-2.0 parts of polyethyleneimine-dopamine copolymer, 3.0-4.0 parts of sulfobetaine methacrylate, 27.0-32.0 parts of epoxidized cardanol-polycaprolactone copolymer, 7.0-10.0 parts of methyltetrahydrophthalic anhydride, 4.5-6.5 parts of sulfobetaine / boron nitride hybrid filler, 6.0-8.0 parts of acrylic acid boric acid core-shell hyperbranched polyester, 0.3-0.5 parts of photoinitiator, 0.3-0.5 parts of leveling agent, and 30.0-35.0 parts of deionized water.
[0053] In some embodiments, the number average molecular weight of the phenylboronic acid functionalized polyethylene glycol is 1800 to 2200, and the phenylboronic acid grafting rate is 85 to 95%; and / or,
[0054] In the polyethyleneimine-dopamine copolymer, the branching degree of polyethyleneimine is 0.35-0.45, and the grafting amount of dopamine is 1.8-2.2 mmol / g; and / or,
[0055] The epoxy value of the epoxidized cardanol-polycaprolactone copolymer is 0.25-0.35 eq / 100 g, and the molecular weight of the polycaprolactone segment is 2000-3000.
[0056] In some embodiments, the core of the acrylic acid boronic acid core-shell hyperbranched polyester is a hyperbranched polyester, the shell is acrylic acid boronic acid, the generation number of the hyperbranched polyester is 3.0-4.0, and the functionality of the acrylic acid boronic acid is 2.8-3.2 mmol / g.
[0057] In some embodiments, in the sulfobetaine / boron nitride hybrid filler, the boron nitride is hexagonal boron nitride, and the sulfobetaine methacrylate is modified on the surface of the hexagonal boron nitride, with the modification amount being 20-25% of the mass of the hexagonal boron nitride.
[0058] In some embodiments, the photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone; and / or,
[0059] The leveling agent is polyether modified siloxane.
[0060] Traditional water-based adhesives are difficult to achieve a balance of water resistance, toughness, and functionality. The fundamental reasons are as follows:
[0061] (1) The contradiction between water resistance and toughness: Water resistance requires a rigid covalent cross-linked network (such as epoxy-amine curing system) or hydrophobic groups (such as long-chain alkyl groups) to reduce water molecule penetration, but the rigid network will restrict the movement of the chain segments and make the material brittle. Toughness requires flexible segments (such as polyether, polyester) or dynamic bonds (such as hydrogen bonds) to absorb external force energy, but the flexible segments are highly hydrophilic (such as polyethylene glycol), which will increase water absorption; dynamic bonds (such as hydrogen bonds) are easily destroyed by water molecules in an aqueous environment, resulting in a decrease in water resistance.
[0062] (2) The contradiction between functionality and structural stability: Functionalities such as wet adhesion and self-repair rely on dynamic interactions (such as borate bonds and metal coordination). However, the reversibility of dynamic bonds weakens the overall strength of the network, resulting in reduced structural stability when the functionality is exerted (such as adhesion attenuation in the wet state). Although traditional covalent cross-linked networks (such as polyurethane and epoxy) have high strength, they lack dynamic response capabilities and cannot give the material environmental adaptability.
[0063] Therefore, this application breaks through this balancing problem from the perspectives of molecular design and network construction by constructing a multi-level collaborative system of "dynamic supramolecular network-covalent cross-linking network-environmental response unit". The specific solution mechanism is as follows:
[0064] (1) Dynamic supramolecular networks: solving the synergistic problem of wet functionality and toughness
[0065] N-(3,4-dihydroxyphenylethyl) methacrylamide: The catechol group in the molecule coordinates with metals (such as Fe 3+) penetrates the water film and forms strong adhesion at the wet interface (bond energy ~150kJ / mol); at the same time, the catechol group and the boronic acid group of phenylboronic acid functionalized polyethylene glycol form a dynamic borate ester bond (BO bond, bond energy ~300kJ / mol), which can reversibly break and reorganize under external force, dissipating energy and improving toughness, thereby improving wet adhesion and toughness.
[0066] Phenylboronic acid functionalized polyethylene glycol: The boronic acid group forms a dynamic BO bond with catechol, while the flexible polyethylene glycol chain segment (Mn=2000) provides chain segment mobility, giving the network both dynamic responsiveness and flexibility. In addition, phenylboronic acid forms a pH-responsive borate ester bond (stable in acid and dissociated in alkaline) with the catechol of N-(3,4-dihydroxyphenylethyl) methacrylamide, achieving self-healing function.
[0067] Polyethyleneimine-dopamine copolymer: The primary amine (-NH2) of polyethyleneimine forms a boron-nitrogen bond (BN bond, bond energy ~200kJ / mol) with the borate ester, which enhances the network rigidity and prevents excessive slippage of the flexible chain segment resulting in a decrease in strength; the catechol of dopamine provides additional Fe 3+ The coordination site (coordination bond energy ~150kJ / mol) anchors the metal substrate and synergizes with the catechol of N-(3,4-dihydroxyphenylethyl) methacrylamide to enhance wet adhesion.
[0068] As a result, the BO and BN bonds synergistically form a reversible crosslinked network. Under external force, the bonds break and absorb energy, and after the stress is relieved, the bonds reform and restore the structure. This ensures wet adhesion (penetrating the water film) while also improving toughness through dynamic energy dissipation. Furthermore, the bond energies of the BO and BN bonds are significantly higher than those of hydrogen bonds (~20 kJ / mol), making them less susceptible to displacement by water molecules in an aqueous environment. This reduces dynamic bond hydrolysis failure and balances functionality and water resistance.
[0069] (2) Covalent cross-linking network: building a water-resistant rigid skeleton and regulating toughness
[0070] Epoxidized cardanol-polycaprolactone copolymer: The long alkyl chain (C18) of cardanol provides hydrophobicity, blocking the penetration of water molecules; the polycaprolactone segment co-crystallizes with the dodecylamine segment of the acrylic boric acid core-shell hyperbranched polyester to form physical cross-linking points, which cooperate with the epoxy-anhydride covalent bond (COC=O, bond energy ~360kJ / mol) to construct a biomimetic structure of "covalent bond rigid domain + crystalline flexible domain": the covalent bond provides strength, and the crystalline phase absorbs impact.
[0071] Methyltetrahydrophthalic anhydride: Methyltetrahydrophthalic anhydride and the epoxy ring-opening polymerization of epoxidized cardanol-polycaprolactone form hydrolysis-resistant ester bonds (COC=O). Compared with traditional epoxy-amine curing systems, the ester bond has a lower hydrolysis rate in a neutral environment, improving long-term water resistance. At the same time, the curing reaction ensures a moderate network crosslinking density, avoiding brittleness caused by excessive rigidity.
[0072] As a result, the flexible polycaprolactone segments of the epoxidized cardanol-polycaprolactone form a microphase-separated structure with the rigid cardanol-epoxy segments. The rigid domains (cardanol and covalent crosslinks) resist external forces, while the flexible domains (polycaprolactone crystalline phase) dissipate energy through chain motion, achieving both high strength and high toughness. Furthermore, the hydrophobic shielding effect of the long alkyl chains combined with the hydrolysis resistance of the covalent ester bonds prevents water molecules from entering the network, preventing the flexible segments from swelling and failing, thus resolving the problem of poor water resistance in traditional flexible materials.
[0073] (3) Environmental response unit: anchoring functional components and enhancing interface stability
[0074] Boronic acid acrylate core-shell hyperbranched polyester: The hyperbranched structure of the core (hyperbranched polyester) provides numerous interfacial contact points, enhancing interaction with the substrate. The carboxyl groups of the acrylic acid in the shell (boronic acid acrylate) react with the epoxy groups of epoxidized cardanol-polycaprolactone to form covalent ester bonds, anchoring the hyperbranched polyester in the covalent network. The boronic acid groups form BO bonds with the boronic acid groups of phenylboronic acid-functionalized polyethylene glycol, connecting the dynamic network and achieving chemical coupling of the "dynamic-covalent" network.
[0075] Sulfobetaine methacrylate: The zwitterionic structure of sulfobetaine inhibits biofouling (such as bacterial adhesion) while enhancing interfacial compatibility (reducing surface energy) and enabling uniform dispersion of dynamic and covalent networks.
[0076] Sulfobetaine / boron nitride hybrid filler: Boron nitride filler fills the network gaps to improve mechanical strength. At the same time, its layered structure hinders the diffusion of water molecules, helping to improve water resistance.
[0077] Photoinitiator: absorbs ultraviolet light to initiate free radical polymerization, accelerating the cross-linking and curing of dynamic networks and covalent networks.
[0078] Leveling agent: reduces surface tension, promotes uniform spreading of adhesive on the substrate surface, and improves interfacial bonding strength.
[0079] Therefore, the acrylic acid boric acid core-shell hyperbranched polyester is doubly anchored by covalent ester bonds and BO bonds, avoiding the shedding problem of traditional physically added fillers and ensuring long-term functionality (such as self-repair and wet adhesion).
[0080] In summary, the water-based adhesive provided in this application achieves a balance between water resistance, toughness, and functionality through a dynamic supramolecular network, a covalent cross-linking network, and an environmentally responsive unit. The principles are summarized as follows:
[0081] (1) Boric acid ester bonds (dynamic) and covalent ester bonds (rigid) form a "double network": the dynamic bond gives the material toughness and self-healing ability, and the covalent bond provides water resistance. The two interpenetrate to avoid the contradiction of traditional adhesives: "water resistance leads to brittleness, and toughening leads to decreased water resistance."
[0082] (2) Environmentally responsive interface regulation: pH-responsive borate ester bonds (acid-stable and alkaline-hydrolyzed) work together with hydrophobic alkyl chains (water-repelling) to maintain adhesion in a wet environment through dynamic bond reorganization. At the same time, the hydrophobic chain reduces water penetration, breaking through the bottleneck of traditional water-based adhesives that "loses adhesion when exposed to water."
[0083] (3) Directed cross-linking of functional groups: catechol (adhesion), boric acid (dynamic cross-linking), epoxy (covalent curing), carboxyl (interface anchoring) and other groups are directionally connected through chemical bonds (boric acid ester bonds, ester bonds, coordination bonds) to form a "strong correlation network" to avoid component agglomeration or phase separation, and achieve a balance between water resistance, toughness and functionality (self-repairing, anti-pollution).
[0084] Figure 1 A schematic flow chart of a method for preparing a water-based adhesive provided in an embodiment of the present application.
[0085] Based on a general inventive concept, such as Figure 1 As shown, the present application provides a method for preparing the water-based adhesive described in any one of the above embodiments, the method comprising the following steps:
[0086] S1, mixing N-(3,4-dihydroxyphenylethyl) methacrylamide, phenylboronic acid functionalized polyethylene glycol, polyethyleneimine-dopamine copolymer, sulfobetaine methacrylate and deionized water, and adjusting the pH to 6.8-7.2 to obtain a first mixed solution;
[0087] Adjusting the pH to 6.8-7.2 stabilizes the system's compatibility, preventing acidic or alkaline conditions from damaging the functional groups (such as phenylboronic acid, hydroxyl groups, and amine groups) in the raw materials, preventing side reactions (such as phenylboronic acid hydrolysis and amine protonation), and ensuring uniform dispersion of the components. Furthermore, the neutral environment facilitates the formation of dynamic hydrogen bonds or boronate ester bonds between the phenolic hydroxyl groups of N-(3,4-dihydroxyphenylethyl)methacrylamide and the dopamine phenolic hydroxyl groups of the polyethyleneimine-dopamine copolymer and the boronic acid groups of the phenylboronic acid-functionalized polyethylene glycol, laying the foundation for subsequent dynamic network construction.
[0088] S2, adding a photoinitiator to the first mixed solution to perform ultraviolet light curing to obtain a second mixed solution;
[0089] In some embodiments, the wavelength of the UV curing is 365 nm, the irradiation time is 5 to 10 min, and the light intensity is 50 to 70 mW / cm 2 .
[0090] Free radical polymerization forms a dynamic borate bond (BO bond) cross-linking network. 365nm wavelength is the best absorption band of the photoinitiator, combined with 50-70mW / cm 2 Light intensity of 5 to 10 minutes can quickly initiate free radical polymerization of double bonds in acrylamide and methacrylate, forming a preliminary covalently cross-linked network and enhancing the adhesive's initial mechanical strength. A 5-10 minute exposure ensures the synergistic formation of dynamic supramolecular interactions (such as borate bonds) and covalent bonds, preventing excessive rigidity from affecting toughness.
[0091] S3, plasma-treating the sulfobetaine / boron nitride hybrid filler to obtain a pretreated filler;
[0092] In some embodiments, the working gas for the plasma treatment is an argon / oxygen mixture with a volume ratio of 4:1, the power is 100 W, and the treatment time is 2 to 5 minutes.
[0093] The physical bombardment of argon can remove pollutants on the surface of the filler, and the chemical oxidation of oxygen can introduce polar groups such as hydroxyl and carboxyl groups, thereby improving the interfacial compatibility between the filler and the polymer matrix and enhancing the dispersion of the filler in the adhesive.
[0094] S4, adding epoxidized cardanol-polycaprolactone copolymer, methyltetrahydrophthalic anhydride and acrylic acid boric acid core-shell hyperbranched polyester to the second mixed solution, then performing stepwise thermal curing, and adding pretreated filler during the stepwise thermal curing process to obtain a third mixed solution;
[0095] In some embodiments, step S4 comprises:
[0096] S401, adding epoxidized cardanol-polycaprolactone copolymer, methyltetrahydrophthalic anhydride and acrylic acid boric acid core-shell hyperbranched polyester to the second mixed solution to obtain a first epoxy mixture;
[0097] S402, heating the first epoxy mixture to 70° C. and keeping the temperature for 2 hours to obtain a second epoxy mixture;
[0098] S403, continuing to heat the second epoxy mixture from 70° C. to 90° C. and keeping the temperature for 1 hour, adding the pretreated filler during the 1 hour of keeping the temperature, to obtain a third epoxy mixture;
[0099] S404, continuing to heat the third epoxy mixture from 90° C. to 120° C. and keeping the temperature for 30 minutes to obtain a third mixed solution.
[0100] Keeping at 70°C for 2 hours can promote the initial ring-opening reaction between the epoxy groups of the epoxidized cardanol-polycaprolactone copolymer and methyltetrahydrophthalic anhydride (anhydride curing agent), forming a partial covalent cross-linked structure, while avoiding thermal decomposition of the polycaprolactone segment caused by excessive temperature and retaining the flexibility of the chain segment.
[0101] The system was kept warm at 90°C for 1 hour and the filler was added. At this time, the viscosity of the system was moderate, which facilitated the uniform dispersion of the pretreated filler. Higher temperatures can enhance the hydrogen bonding between the polar groups on the filler surface and the polymer matrix, thereby improving the interfacial bonding strength. At the same time, the boronic acid groups of the acrylic acid boric acid core-shell hyperbranched polyester can further form dynamic borate ester bonds with the hydroxyl groups in the system, thereby enhancing the network toughness.
[0102] The material was kept at 120°C for 30 minutes. The high temperature promoted the complete epoxy-anhydride reaction to form a dense covalent cross-linked network (rigid support skeleton). At the same time, the dynamic supramolecular network (such as borate bonds and hydrogen bonds) remained reversible at high temperature, avoiding excessive hardening of the system and balancing rigidity and toughness.
[0103] S5. Add a leveling agent to the third mixed liquid cooled to room temperature to obtain a water-based adhesive.
[0104] Polyether-modified siloxane can quickly migrate to the adhesive surface, evenly reduce surface tension, eliminate defects such as shrinkage holes and orange peel during coating, and improve film smoothness.
[0105] In some embodiments, the preparation method of the sulfobetaine / boron nitride hybrid filler comprises:
[0106] dispersing hexagonal boron nitride powder in concentrated nitric acid to perform surface hydroxylation on the hexagonal boron nitride to obtain activated hexagonal boron nitride;
[0107] The activated hexagonal boron nitride is dispersed in deionized water, and then sulfobetaine methacrylate monomer and azobisisobutylamidine hydrochloride are added, and a graft polymerization reaction is carried out under nitrogen protection to covalently bond the sulfobetaine methacrylate to the surface of the hexagonal boron nitride to obtain the sulfobetaine / boron nitride hybrid filler;
[0108] Wherein, the mass of the sulfobetaine methacrylate monomer is 20% to 25% of the mass of the hexagonal boron nitride;
[0109] The mass of the azobisisobutylamidine hydrochloride is 1% to 2% of the mass of the sulfobetaine methacrylate monomer;
[0110] The graft polymerization reaction temperature is 60-70° C. and the reaction time is 8-12 hours.
[0111] The oxidation of concentrated nitric acid generates hydroxyl groups on the surface of boron nitride, which provides covalent bonding sites for the subsequent grafting of sulfobetaine methacrylate and enhances the chemical bonding between the filler and the polymer matrix.
[0112] In some embodiments, the method for preparing the acrylic acid boric acid core-shell hyperbranched polyester comprises:
[0113] Pentaerythritol, malonic anhydride and p-toluenesulfonic acid are dissolved in xylene solvent to carry out polycondensation reaction to obtain hyperbranched polyester;
[0114] The hyperbranched polyester is dissolved in tetrahydrofuran, and then acrylic acid boronic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are added to introduce acrylic acid boronic acid groups into the terminal hydroxyl groups of the hyperbranched polyester to obtain the acrylic acid boronic acid core-shell hyperbranched polyester;
[0115] Wherein, the molar ratio of the pentaerythritol to the malonic anhydride is 1:(3-4);
[0116] The mass of the p-toluenesulfonic acid is 0.5 to 1.5% of the total mass of the pentaerythritol and the malonic anhydride;
[0117] The polycondensation reaction temperature is 140-160°C and the time is 4-6 hours;
[0118] The functionality of the acrylic acid boronic acid is 2.8 to 3.2 mmol / g, and the molar ratio of the acrylic acid boronic acid to the hydroxyl group of the hyperbranched polyester is (1 to 1.2):1;
[0119] The molar ratio of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to the acrylic acid boric acid is (1.5-2.0):1;
[0120] The thickness of the acrylic acid boric acid shell layer is 5 to 10 nm.
[0121] The molar ratio of pentaerythritol to malonic anhydride determines the generation of the hyperbranched polyester (3.0-4.0). The high-generation branched structure can provide a large number of terminal hydroxyl groups, providing sites for subsequent acrylic acid and boric acid grafting. At the same time, the branched chain segments can enhance the flexibility of the network.
[0122] The molar ratio of acrylic acid, boric acid and hydroxyl groups is controlled at (1-1.2):1, which can form a boric acid shell with a functionality of 2.8-3.2 mmol / g on the surface of the hyperbranched polyester. The shell thickness of 5-10 nm can ensure the exposure of the boronic acid groups (to participate in the formation of dynamic borate ester bonds) while avoiding the shell being too thick, which may hinder the movement of the molecular chain and affect the toughness.
[0123] In this application, the pH adjustment of S1 and the step-by-step thermal curing of S4 synergistically promote the formation of reversible dynamic bonds among phenylboronic acid, phenolic hydroxyl groups, etc., giving the adhesive wet adhesion and toughness; the ultraviolet light curing of S2 and the high-temperature thermal curing of S4 step-by-step construct a covalent cross-linked network to provide rigid support; the plasma treatment of S3 and the optimization of the filler addition timing of S4 ensure that the hexagonal boron nitride is evenly dispersed and strongly bonded to the matrix, thereby improving water resistance and mechanical properties.
[0124] The water-based adhesive provided in this application breaks through the bottleneck of traditional water-based adhesives in balancing water resistance, toughness, and functionality through innovative ingredient design, multi-level network construction, and precise preparation technology. Its core advantages are summarized as follows:
[0125] 1. Performance Balance Advantage: Breaking through Traditional Contradictions and Achieving Multi-Performance Collaborative Improvement
[0126] (1) Significantly improved water resistance: The dual mechanism of hydrophobicity and hydrolysis resistance: the C18 long alkyl chain (contact angle >90°) and hydrolysis-resistant ester bond (bond energy ~360kJ / mol) of the epoxidized cardanol-polycaprolactone copolymer synergistically block water penetration, resulting in a water absorption rate of <5%, which is superior to traditional water-based adhesives (water absorption rate >15%). Dynamic bonds resist water damage. The borate ester bond (BO, 300kJ / mol) and boron nitrogen bond (BN, 200kJ / mol) have bond energies higher than those of water molecules, making them less susceptible to hydrolysis failure in humid environments and maintaining network stability.
[0127] (2) Simultaneous optimization of toughness and mechanical strength: The rigid-flexible network structure, the dynamic supramolecular network (reversible energy dissipation of BO / BN bonds) and the covalent-crystalline double crosslinking (ester bond rigid domain + polycaprolactone crystalline flexible domain) work together to increase the elongation at break to 110% (traditional adhesives <50%) while maintaining tensile strength above 15 MPa. The biomimetic energy dissipation mechanism simulates the catechol adhesion of mussel byssus and the "rigid-flexible phase separation" structure of biomaterials. Under external force, dynamic bond reorganization and crystal phase slip jointly dissipate energy, avoiding brittle fracture.
[0128] (3) Comprehensively enhanced functionality and long-term stability: pH-responsive self-repairing, the borate bond, which is stable in acidic conditions (pH < 7) and dissociates in alkaline conditions (pH > 9), achieves a self-repair efficiency of > 90%, and can be repaired more than 5 times, solving the problem of irreversible damage in traditional adhesives. Strong wet adhesion and anti-fouling properties, the catechol-metal coordination (bond energy ~ 150 kJ / mol) penetrates the water film, and the adhesion strength at the wet interface reaches 4.7 kN / m (traditional adhesives < 1 kN / m); the zwitterionic structure of sulfobetaine inhibits biological contamination by > 95%, making it suitable for harsh scenarios such as marine and medical applications.
[0129] 2. Molecular Design Advantages: Multi-level Network Collaboration to Achieve Directed Regulation of Functional Groups
[0130] (1) Dynamic-covalent double network interpenetrating structure: N-(3,4-dihydroxyphenylethyl)methacrylamide, phenylboronic acid functionalized polyethylene glycol, and polyethyleneimine-dopamine copolymer form reversible crosslinks through BO / BN bonds, giving the material environmental responsiveness and toughness. Epoxidized cardanol-polycaprolactone copolymer and methyltetrahydrophthalic anhydride form a rigid skeleton through ester bonds, providing water-resistant support. The two are coupled through the double chemical bond (BO bond + ester bond) of the acrylic acid boric acid core-shell hyperbranched polyester to avoid phase separation.
[0131] (2) Anchoring and regulation of environmental response units: The core-shell hyperbranched polyester acts as a bridge. The core dodecylamine drives water, while the shell acrylic acid boric acid is anchored in the double network through covalent ester bonds and BO bonds, achieving a "water drive-anchoring" synergistic effect. The filler shedding rate is reduced from >30% to 0. Sulfobetaine methacrylate and the hybrid filler synergistically reduce the surface energy, improve compatibility, and inhibit the interfacial adsorption of water molecules and biological pollutants.
[0132] 3. Preparation process advantages: precise control to ensure performance consistency and reliability
[0133] (1) Step curing and simultaneous formation of dynamic bonds: UV curing (S2) with a wavelength of 365 nm and 5-10 min irradiation quickly initiates double bond polymerization, forming a preliminary network and retaining the activity of dynamic bonds. Step thermal curing (S4) with stepwise curing from 70°C to 90°C to 120°C balances the degree of epoxy-anhydride reaction with the crystallinity of polycaprolactone, avoids segment degradation caused by high temperature, and ensures a balance between elongation at break and water resistance.
[0134] (2) Filler surface modification and precise addition: Plasma treatment (S3) was performed in an argon / oxygen (4:1) mixture at 100W for 2-5 minutes to introduce polar groups onto the hexagonal boron nitride surface. Combined with a 20%-25% sulfobetaine grafting amount, the filler dispersed particle size was reduced to <1μm, and the mechanical reinforcement effect was improved by 40%. Filler (S403) was added during the thermal curing process. At 90°C, the system viscosity was moderate, the filler was evenly dispersed, and hydrogen and chemical bonds were formed with the matrix to prevent sedimentation or agglomeration.
[0135] 4. Application Scenario Advantages: Broad Spectrum Adaptability and Environmental Friendliness
[0136] (1) Reliability in complex environments: Suitable for use in humid (marine engineering, bathroom tile pasting), high temperature (automotive engine sealing), and easily contaminated (medical equipment, food packaging) environments. Compared to traditional adhesives, the service life is extended by 3 to 5 times. Light-induced rapid curing (5 to 10 minutes) is compatible with thermal curing, meeting the requirements of different construction processes (such as UV on-site curing and thermal curing industrial production lines).
[0137] (2) Green and environmentally friendly characteristics: It uses water as solvent, and the volatile organic compound (VOC) content is <1g / L (traditional solvent-based adhesives are >500g / L), which meets environmental protection standards; the raw materials do not contain heavy metals, formaldehyde and other harmful substances, and are suitable for food contact materials and medical fields.
[0138] The present application will be further described below in conjunction with specific examples. It should be understood that these examples are intended to illustrate the present application only and are not intended to limit the scope of the present application. The experimental methods in the following examples where specific conditions are not specified are generally measured according to industry standards. If there are no corresponding industry standards, then the methods are carried out according to general international standards, conventional conditions, or the conditions recommended by the manufacturer.
[0139] Example 1
[0140] This embodiment provides a water-based adhesive, which is composed of the following chemical components, in parts by mass: 4.25 parts of N-(3,4-dihydroxyphenylethyl)methacrylamide (CAS No.: 471915-89-6), 3.0 parts of phenylboronic acid functionalized polyethylene glycol, 1.6 parts of polyethyleneimine-dopamine copolymer, sulfobetaine methacrylate (3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]-1,1-diol ... ]ammonium]propane-1-sulfonic acid inner salt, abbreviated as SBMA, CAS No. 3637-26-1) 3.5 parts, epoxidized cardanol-polycaprolactone copolymer 29.5 parts, methyltetrahydrophthalic anhydride (CAS No. 11070-44-3) 8.5 parts, sulfobetaine / boron nitride hybrid filler 5.5 parts, acrylic acid boric acid core-shell hyperbranched polyester 7.0 parts, photoinitiator 0.4 part, leveling agent 0.4 part, and deionized water 32.5 parts.
[0141] The number average molecular weight of the phenylboronic acid functionalized polyethylene glycol is about 2000, and the phenylboronic acid grafting rate is about 90%;
[0142] In the polyethyleneimine-dopamine copolymer, the branching degree of polyethyleneimine is about 0.35-0.45, and the dopamine grafting amount is about 2.0 mmol / g;
[0143] The epoxy value of the epoxidized cardanol-polycaprolactone copolymer is about 0.30 eq / 100 g, and the molecular weight of the polycaprolactone segment is about 2500.
[0144] The core of the acrylic acid boronic acid core-shell hyperbranched polyester is a hyperbranched polyester, and the shell is acrylic acid boronic acid. The generation number of the hyperbranched polyester is about 3.5, and the functionality of the acrylic acid boronic acid is about 3.0 mmol / g.
[0145] In the sulfobetaine / boron nitride hybrid filler, the boron nitride is hexagonal boron nitride, and the sulfobetaine methacrylate is modified on the surface of the hexagonal boron nitride, with the modification amount being 23% of the mass of the hexagonal boron nitride.
[0146] The photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone (CAS No. 106797-53-9);
[0147] The leveling agent is polyether modified siloxane (model: AC-8306).
[0148] Based on the above water-based adhesive, this embodiment also provides a method for preparing the water-based adhesive described in the above embodiment, the method comprising the following steps:
[0149] S1, mixing N-(3,4-dihydroxyphenylethyl) methacrylamide, phenylboronic acid functionalized polyethylene glycol, polyethyleneimine-dopamine copolymer, sulfobetaine methacrylate and deionized water, and adjusting the pH to 7.0 to obtain a first mixed solution;
[0150] S2, adding a photoinitiator to the first mixed solution to perform ultraviolet light curing to obtain a second mixed solution;
[0151] The wavelength of the UV curing was 365 nm, the irradiation time was 8 min, and the light intensity was 60 mW / cm 2 .
[0152] S3, plasma-treating the sulfobetaine / boron nitride hybrid filler to obtain a pretreated filler;
[0153] The working gas for the plasma treatment is an argon / oxygen mixture with a volume ratio of 4:1, the power is 100 W, and the treatment time is 3.5 minutes.
[0154] S4. Add epoxidized cardanol-polycaprolactone copolymer, methyltetrahydrophthalic anhydride and acrylic acid boric acid core-shell hyperbranched polyester to the second mixed solution to obtain a first epoxy mixture; heat the first epoxy mixture to 70°C and keep it warm for 2 hours to obtain a second epoxy mixture; continue to heat the second epoxy mixture from 70°C to 90°C and keep it warm for 1 hour, and add pretreated filler during the 1 hour insulation process to obtain a third epoxy mixture; continue to heat the third epoxy mixture from 90°C to 120°C and keep it warm for 30 minutes to obtain a third mixed solution.
[0155] S5. Add a leveling agent to the third mixed liquid cooled to room temperature to obtain a water-based adhesive.
[0156] The preparation method of the sulfobetaine / boron nitride hybrid filler includes: dispersing hexagonal boron nitride powder in concentrated nitric acid to perform surface hydroxylation on the hexagonal boron nitride to obtain activated hexagonal boron nitride; dispersing the activated hexagonal boron nitride in deionized water, adding sulfobetaine methacrylate monomer and azobisisobutylamidine hydrochloride, and performing a graft polymerization reaction under nitrogen protection to covalently bond the sulfobetaine methacrylate to the surface of the hexagonal boron nitride to obtain the sulfobetaine / boron nitride hybrid filler; wherein the mass of the sulfobetaine methacrylate monomer is 23% of the mass of the hexagonal boron nitride; the mass of the azobisisobutylamidine hydrochloride is 1.5% of the mass of the sulfobetaine methacrylate monomer; and the temperature of the graft polymerization reaction is 65° C. and the time is 10 hours.
[0157] The preparation method of the acrylic acid boric acid core-shell hyperbranched polyester comprises: dissolving pentaerythritol, malonic anhydride and p-toluenesulfonic acid in a xylene solvent to carry out a polycondensation reaction to obtain a hyperbranched polyester; dissolving the hyperbranched polyester in tetrahydrofuran, and then adding acrylic acid boric acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to introduce acrylic acid boric acid groups on the terminal hydroxyl groups of the hyperbranched polyester to obtain the acrylic acid boric acid core-shell hyperbranched polyester; wherein the molar ratio of the pentaerythritol to the malonic anhydride is 1:3.5; the mass of the p-toluenesulfonic acid is 1.0% of the total mass of the pentaerythritol and the malonic anhydride; the temperature of the polycondensation reaction is 150° C., and the time is 5 hours; the functionality of the acrylic boronic acid is 3.0 mmol / g, and the molar ratio of the acrylic boronic acid to the hydroxyl group of the hyperbranched polyester is 1.1:1; the molar ratio of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to the acrylic boronic acid is 1.8:1; and the thickness of the acrylic boronic acid shell is approximately 8 nm.
[0158] The preparation method of phenylboronic acid-functionalized polyethylene glycol includes dissolving HOOC-PEG-OH (1 mmol) in anhydrous DMF, adding EDC (1.2 mmol) and NHS (1.2 mmol), and stirring at room temperature in the dark for 2 hours to generate an active NHS ester. 4-Aminophenylboronic acid (1.2 mmol) is then added to the active NHS ester, the pH is adjusted to 8.0, and the reaction is carried out at room temperature for 12 hours. Excess glycine (50 mM) is then added to quench unreacted active groups, thereby obtaining phenylboronic acid-functionalized polyethylene glycol.
[0159] The preparation method of the polyethyleneimine-dopamine copolymer includes dissolving dopamine hydrochloride (0.4 g) in tris (hydroxymethylaminomethane) buffer (pH 8.5), ultrasonically dispersing until completely dissolved, then adding polyethyleneimine (at a mass ratio of twice that of dopamine hydrochloride), and stirring to mix thoroughly. Stirring is performed at room temperature in the dark for 12 hours, utilizing the self-polymerization of dopamine hydrochloride to form polydopamine, which is then cross-linked with polyethyleneimine via a Schiff base reaction or a Michael addition reaction. The reaction solution is then centrifuged (10,000 rpm, 30 minutes) to remove unreacted free dopamine and polyethyleneimine, and freeze-dried to obtain polyethyleneimine-dopamine copolymer powder.
[0160] The preparation method of the epoxidized cardanol-polycaprolactone copolymer includes: dissolving cardanol (purity ≥95%) and hydrogen peroxide (mass ratio 1:1.5) in acetic acid (pH 4), stirring at room temperature for 30 minutes to activate the phenolic hydroxyl groups, adding epichlorohydrin (molar ratio of cardanol:epichlorohydrin = 1:1.2), heating to 60°C and reacting for 5 hours to generate epoxidized cardanol glycidyl ether. Epoxidized cardanol glycidyl ether was dissolved in tetrahydrofuran, and tetrabutylammonium bromide (catalyst, mass ratio 1:0.05) was added and stirred at 50°C for 2 hours to open the epoxy group to generate hydroxyl active sites. The activated epoxidized cardanol was mixed with polycaprolactone (molar ratio 1:10-1:20, polycaprolactone CAS number 36890-68-3) and stannous octoate catalyst (molar ratio 0.001). The temperature was raised to 120°C under nitrogen protection and the reaction was reacted for 48 hours. After removing the solvent, the epoxidized cardanol-polycaprolactone copolymer was obtained.
[0161] Example 2
[0162] This embodiment provides a water-based adhesive, which is composed of the following chemical components, in parts by mass: 3.5 parts of N-(3,4-dihydroxyphenylethyl)methacrylamide (CAS No.: 471915-89-6), 2.5 parts of phenylboronic acid functionalized polyethylene glycol, 1.2 parts of polyethyleneimine-dopamine copolymer, sulfobetaine methacrylate (3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]-1-[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[ ]ammonium]propane-1-sulfonic acid inner salt, abbreviated as SBMA, CAS No. 3637-26-1) 3.0 parts, epoxidized cardanol-polycaprolactone copolymer 27.0 parts, methyltetrahydrophthalic anhydride (CAS No. 11070-44-3) 7.0 parts, sulfobetaine / boron nitride hybrid filler 4.5 parts, acrylic acid boric acid core-shell hyperbranched polyester 6.0 parts, photoinitiator 0.3 parts, leveling agent 0.3 parts, and deionized water 35.0 parts.
[0163] The number average molecular weight of the phenylboronic acid functionalized polyethylene glycol is about 1800, and the phenylboronic acid grafting rate is about 85%;
[0164] In the polyethyleneimine-dopamine copolymer, the branching degree of polyethyleneimine is about 0.35 to 0.45, and the dopamine grafting amount is about 1.8 mmol / g;
[0165] The epoxy value of the epoxidized cardanol-polycaprolactone copolymer is about 0.25eq / 100g, and the molecular weight of the polycaprolactone segment is about 2000.
[0166] The core of the acrylic acid boronic acid core-shell hyperbranched polyester is a hyperbranched polyester, and the shell is acrylic acid boronic acid. The generation number of the hyperbranched polyester is about 3.0, and the functionality of the acrylic acid boronic acid is about 2.8 mmol / g.
[0167] In the sulfobetaine / boron nitride hybrid filler, the boron nitride is hexagonal boron nitride, and the sulfobetaine methacrylate is modified on the surface of the hexagonal boron nitride, with the modification amount being 20% of the mass of the hexagonal boron nitride.
[0168] The photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone (CAS No. 106797-53-9);
[0169] The leveling agent is polyether modified siloxane (model: AC-8306).
[0170] Based on the above water-based adhesive, this embodiment also provides a method for preparing the water-based adhesive described in the above embodiment, the method comprising the following steps:
[0171] S1, mixing N-(3,4-dihydroxyphenylethyl) methacrylamide, phenylboronic acid functionalized polyethylene glycol, polyethyleneimine-dopamine copolymer, sulfobetaine methacrylate and deionized water, and adjusting the pH to 6.8 to obtain a first mixed solution;
[0172] S2, adding a photoinitiator to the first mixed solution to perform ultraviolet light curing to obtain a second mixed solution;
[0173] The wavelength of the UV curing was 365 nm, the irradiation time was 5 min, and the light intensity was 70 mW / cm 2 .
[0174] S3, plasma-treating the sulfobetaine / boron nitride hybrid filler to obtain a pretreated filler;
[0175] The working gas for the plasma treatment is an argon / oxygen mixture with a volume ratio of 4:1, the power is 100 W, and the treatment time is 2 minutes.
[0176] S4. Add epoxidized cardanol-polycaprolactone copolymer, methyltetrahydrophthalic anhydride and acrylic acid boric acid core-shell hyperbranched polyester to the second mixed solution to obtain a first epoxy mixture; heat the first epoxy mixture to 70°C and keep it warm for 2 hours to obtain a second epoxy mixture; continue to heat the second epoxy mixture from 70°C to 90°C and keep it warm for 1 hour, and add pretreated filler during the 1 hour insulation process to obtain a third epoxy mixture; continue to heat the third epoxy mixture from 90°C to 120°C and keep it warm for 30 minutes to obtain a third mixed solution.
[0177] S5. Add a leveling agent to the third mixed liquid cooled to room temperature to obtain a water-based adhesive.
[0178] The preparation method of the sulfobetaine / boron nitride hybrid filler includes: dispersing hexagonal boron nitride powder in concentrated nitric acid to perform surface hydroxylation on the hexagonal boron nitride to obtain activated hexagonal boron nitride; dispersing the activated hexagonal boron nitride in deionized water, adding sulfobetaine methacrylate monomer and azobisisobutylamidine hydrochloride, and performing a graft polymerization reaction under nitrogen protection to covalently bond sulfobetaine methacrylate to the surface of the hexagonal boron nitride to obtain the sulfobetaine / boron nitride hybrid filler; wherein the mass of the sulfobetaine methacrylate monomer is 20% of the mass of the hexagonal boron nitride; the mass of the azobisisobutylamidine hydrochloride is 1% of the mass of the sulfobetaine methacrylate monomer; and the temperature of the graft polymerization reaction is 60°C and the time is 12 hours.
[0179] The preparation method of the acrylic acid boric acid core-shell hyperbranched polyester comprises: dissolving pentaerythritol, malonic anhydride and p-toluenesulfonic acid in a xylene solvent to carry out a condensation reaction to obtain a hyperbranched polyester; dissolving the hyperbranched polyester in tetrahydrofuran, and then adding acrylic acid boric acid and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride to introduce acrylic acid boric acid groups on the terminal hydroxyl groups of the hyperbranched polyester to obtain the acrylic acid boric acid core-shell hyperbranched polyester; wherein the molar ratio of the pentaerythritol to the malonic anhydride is 0. The ratio is 1:3; the mass of the p-toluenesulfonic acid is 0.5% of the total mass of the pentaerythritol and the malonic anhydride; the temperature of the polycondensation reaction is 140° C., and the time is 6 hours; the functionality of the acrylic boronic acid is 2.8 mmol / g, and the molar ratio of the acrylic boronic acid to the hydroxyl group of the hyperbranched polyester is 1:1; the molar ratio of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to the acrylic boronic acid is 1.5:1; and the thickness of the acrylic boronic acid shell is about 5 nm.
[0180] The preparation method of phenylboronic acid-functionalized polyethylene glycol includes dissolving HOOC-PEG-OH (1 mmol) in anhydrous DMF, adding EDC (1.2 mmol) and NHS (1.2 mmol), and stirring at room temperature in the dark for 2 hours to generate an active NHS ester. 4-Aminophenylboronic acid (1.2 mmol) is then added to the active NHS ester, the pH is adjusted to 8.0, and the reaction is carried out at room temperature for 12 hours. Excess glycine (50 mM) is then added to quench unreacted active groups, thereby obtaining phenylboronic acid-functionalized polyethylene glycol.
[0181] The preparation method of the polyethyleneimine-dopamine copolymer includes dissolving dopamine hydrochloride (0.4 g) in tris (hydroxymethylaminomethane) buffer (pH 8.5), ultrasonically dispersing until completely dissolved, then adding polyethyleneimine (at a mass ratio of twice that of dopamine hydrochloride), and stirring to mix thoroughly. Stirring is performed at room temperature in the dark for 12 hours, utilizing the self-polymerization of dopamine hydrochloride to form polydopamine, which is then cross-linked with polyethyleneimine via a Schiff base reaction or a Michael addition reaction. The reaction solution is then centrifuged (10,000 rpm, 30 minutes) to remove unreacted free dopamine and polyethyleneimine, and freeze-dried to obtain polyethyleneimine-dopamine copolymer powder.
[0182] The preparation method of the epoxidized cardanol-polycaprolactone copolymer includes: dissolving cardanol (purity ≥95%) and hydrogen peroxide (mass ratio 1:1.5) in acetic acid (pH 4), stirring at room temperature for 30 minutes to activate the phenolic hydroxyl groups, adding epichlorohydrin (molar ratio of cardanol:epichlorohydrin = 1:1.2), heating to 60°C and reacting for 5 hours to generate epoxidized cardanol glycidyl ether. Epoxidized cardanol glycidyl ether was dissolved in tetrahydrofuran, and tetrabutylammonium bromide (catalyst, mass ratio 1:0.05) was added and stirred at 50°C for 2 hours to open the epoxy group to generate hydroxyl active sites. The activated epoxidized cardanol was mixed with polycaprolactone (molar ratio 1:10-1:20, polycaprolactone CAS number 36890-68-3) and stannous octoate catalyst (molar ratio 0.001). The temperature was raised to 120°C under nitrogen protection and the reaction was reacted for 48 hours. After removing the solvent, the epoxidized cardanol-polycaprolactone copolymer was obtained.
[0183] Example 3
[0184] This embodiment provides a water-based adhesive, which is composed of the following chemical components, in parts by mass: 5.0 parts of N-(3,4-dihydroxyphenylethyl)methacrylamide (CAS No.: 471915-89-6), 3.5 parts of phenylboronic acid functionalized polyethylene glycol, 2.0 parts of polyethyleneimine-dopamine copolymer, sulfobetaine methacrylate (3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl] 4.0 parts of [ammonium] propane-1-sulfonic acid inner salt, abbreviated as SBMA, CAS No. 3637-26-1), 32.0 parts of epoxidized cardanol-polycaprolactone copolymer, 10.0 parts of methyltetrahydrophthalic anhydride (CAS No. 11070-44-3), 6.5 parts of sulfobetaine / boron nitride hybrid filler, 8.0 parts of acrylic acid boric acid core-shell hyperbranched polyester, 0.5 parts of photoinitiator, 0.5 parts of leveling agent, and 30.0 parts of deionized water.
[0185] The number average molecular weight of the phenylboronic acid functionalized polyethylene glycol is about 2200, and the phenylboronic acid grafting rate is about 95%;
[0186] In the polyethyleneimine-dopamine copolymer, the branching degree of polyethyleneimine is about 0.45, and the dopamine grafting amount is about 2.2 mmol / g;
[0187] The epoxy value of the epoxidized cardanol-polycaprolactone copolymer is about 0.35 eq / 100 g, and the molecular weight of the polycaprolactone segment is about 3000.
[0188] The core of the acrylic acid boronic acid core-shell hyperbranched polyester is a hyperbranched polyester, and the shell is acrylic acid boronic acid. The generation number of the hyperbranched polyester is about 4.0, and the functionality of the acrylic acid boronic acid is about 3.2 mmol / g.
[0189] In the sulfobetaine / boron nitride hybrid filler, the boron nitride is hexagonal boron nitride, and the sulfobetaine methacrylate is modified on the surface of the hexagonal boron nitride, with the modification amount being 25% of the mass of the hexagonal boron nitride.
[0190] The photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone (CAS No. 106797-53-9);
[0191] The leveling agent is polyether modified siloxane (model: AC-8306).
[0192] Based on the above water-based adhesive, this embodiment also provides a method for preparing the water-based adhesive described in the above embodiment, the method comprising the following steps:
[0193] S1, mixing N-(3,4-dihydroxyphenylethyl) methacrylamide, phenylboronic acid functionalized polyethylene glycol, polyethyleneimine-dopamine copolymer, sulfobetaine methacrylate and deionized water, and adjusting the pH to 7.2 to obtain a first mixed solution;
[0194] S2, adding a photoinitiator to the first mixed solution to perform ultraviolet light curing to obtain a second mixed solution;
[0195] The wavelength of the UV curing is 365 nm, the irradiation time is 10 min, and the light intensity is 50 mW / cm 2 .
[0196] S3, plasma-treating the sulfobetaine / boron nitride hybrid filler to obtain a pretreated filler;
[0197] The working gas for the plasma treatment is an argon / oxygen mixture with a volume ratio of 4:1, the power is 100 W, and the treatment time is 5 minutes.
[0198] S4. Add epoxidized cardanol-polycaprolactone copolymer, methyltetrahydrophthalic anhydride and acrylic acid boric acid core-shell hyperbranched polyester to the second mixed solution to obtain a first epoxy mixture; heat the first epoxy mixture to 70°C and keep it warm for 2 hours to obtain a second epoxy mixture; continue to heat the second epoxy mixture from 70°C to 90°C and keep it warm for 1 hour, and add pretreated filler during the 1 hour insulation process to obtain a third epoxy mixture; continue to heat the third epoxy mixture from 90°C to 120°C and keep it warm for 30 minutes to obtain a third mixed solution.
[0199] S5. Add a leveling agent to the third mixed liquid cooled to room temperature to obtain a water-based adhesive.
[0200] The preparation method of the sulfobetaine / boron nitride hybrid filler includes: dispersing hexagonal boron nitride powder in concentrated nitric acid to perform surface hydroxylation on the hexagonal boron nitride to obtain activated hexagonal boron nitride; dispersing the activated hexagonal boron nitride in deionized water, adding sulfobetaine methacrylate monomer and azobisisobutylamidine hydrochloride, and performing a graft polymerization reaction under nitrogen protection to covalently bond the sulfobetaine methacrylate to the surface of the hexagonal boron nitride to obtain the sulfobetaine / boron nitride hybrid filler; wherein the mass of the sulfobetaine methacrylate monomer is 25% of the mass of the hexagonal boron nitride; the mass of the azobisisobutylamidine hydrochloride is 2% of the mass of the sulfobetaine methacrylate monomer; and the temperature of the graft polymerization reaction is 70°C and the time is 12 hours.
[0201] The preparation method of the acrylic acid boric acid core-shell hyperbranched polyester comprises: dissolving pentaerythritol, malonic anhydride and p-toluenesulfonic acid in a xylene solvent to carry out a polycondensation reaction to obtain a hyperbranched polyester; dissolving the hyperbranched polyester in tetrahydrofuran, and then adding acrylic acid boric acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to introduce acrylic acid boric acid groups on the terminal hydroxyl groups of the hyperbranched polyester to obtain the acrylic acid boric acid core-shell hyperbranched polyester; wherein the molar ratio of the pentaerythritol to the malonic anhydride is 1:4; the mass of the p-toluenesulfonic acid is 1.5% of the total mass of the pentaerythritol and the malonic anhydride; the temperature of the polycondensation reaction is 160° C., and the time is 4 hours; the functionality of the acrylic boronic acid is 3.2 mmol / g, and the molar ratio of the acrylic boronic acid to the hydroxyl group of the hyperbranched polyester is 1.2:1; the molar ratio of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to the acrylic boronic acid is 2.0:1; and the thickness of the acrylic boronic acid shell is about 10 nm.
[0202] The preparation method of phenylboronic acid-functionalized polyethylene glycol includes dissolving HOOC-PEG-OH (1 mmol) in anhydrous DMF, adding EDC (1.2 mmol) and NHS (1.2 mmol), and stirring at room temperature in the dark for 2 hours to generate an active NHS ester. 4-Aminophenylboronic acid (1.2 mmol) is then added to the active NHS ester, the pH is adjusted to 8.0, and the reaction is carried out at room temperature for 12 hours. Excess glycine (50 mM) is then added to quench unreacted active groups, thereby obtaining the phenylboronic acid-functionalized polyethylene glycol.
[0203] The preparation method of the polyethyleneimine-dopamine copolymer includes dissolving dopamine hydrochloride (0.4 g) in tris (hydroxymethylaminomethane) buffer (pH 8.5), ultrasonically dispersing until completely dissolved, then adding polyethyleneimine (at a mass ratio of twice that of dopamine hydrochloride), and stirring to mix thoroughly. Stirring is performed at room temperature in the dark for 12 hours, utilizing the self-polymerization of dopamine hydrochloride to form polydopamine, which is then cross-linked with polyethyleneimine via a Schiff base reaction or a Michael addition reaction. The reaction solution is then centrifuged (10,000 rpm, 30 minutes) to remove unreacted free dopamine and polyethyleneimine, and freeze-dried to obtain polyethyleneimine-dopamine copolymer powder.
[0204] The preparation method of the epoxidized cardanol-polycaprolactone copolymer includes: dissolving cardanol (purity ≥95%) and hydrogen peroxide (mass ratio 1:1.5) in acetic acid (pH 4), stirring at room temperature for 30 minutes to activate the phenolic hydroxyl groups, adding epichlorohydrin (molar ratio of cardanol:epichlorohydrin = 1:1.2), heating to 60°C and reacting for 5 hours to generate epoxidized cardanol glycidyl ether. Epoxidized cardanol glycidyl ether was dissolved in tetrahydrofuran, and tetrabutylammonium bromide (catalyst, mass ratio 1:0.05) was added and stirred at 50°C for 2 hours to open the epoxy group to generate hydroxyl active sites. The activated epoxidized cardanol was mixed with polycaprolactone (molar ratio 1:10-1:20, polycaprolactone CAS number 36890-68-3) and stannous octoate catalyst (molar ratio 0.001). The temperature was raised to 120°C under nitrogen protection and the reaction was reacted for 48 hours. After removing the solvent, the epoxidized cardanol-polycaprolactone copolymer was obtained.
[0205] Comparative Example 1
[0206] This comparative example is modified as follows based on Example 1:
[0207] The water-based adhesive does not contain N-(3,4-dihydroxyphenylethyl) methacrylamide.
[0208] Comparative Example 2
[0209] This comparative example is modified as follows based on Example 1:
[0210] The water-based adhesive does not contain phenylboronic acid functionalized polyethylene glycol.
[0211] Comparative Example 3
[0212] This comparative example is modified as follows based on Example 1:
[0213] The water-based adhesive does not contain polyethyleneimine-dopamine copolymer.
[0214] Comparative Example 4
[0215] This comparative example is modified as follows based on Example 1:
[0216] The water-based adhesive does not contain sulfobetaine methacrylate.
[0217] Comparative Example 5
[0218] This comparative example is modified as follows based on Example 1:
[0219] The water-based adhesive does not contain epoxidized cardanol-polycaprolactone copolymer.
[0220] Comparative Example 6
[0221] This comparative example is modified as follows based on Example 1:
[0222] The water-based adhesive does not contain methyltetrahydrophthalic anhydride.
[0223] Comparative Example 7
[0224] This comparative example is modified as follows based on Example 1:
[0225] The water-based adhesive does not contain sulfobetaine / boron nitride hybrid filler.
[0226] Comparative Example 8
[0227] This comparative example is modified as follows based on Example 1:
[0228] The water-based adhesive does not contain acrylic boric acid core-shell hyperbranched polyester.
[0229] The performance of the water-based adhesives obtained in Examples 1 to 3 and Comparative Examples 1 to 8 was measured, and the results are shown in Table 1. The specific performance measurement method is as follows:
[0230] Tensile strength and elongation at break: The standard is ASTM D638. The method is to apply the adhesive into a 1mm thick film, cut it into dumbbell-shaped specimens after curing, and stretch it at a rate of 50mm / min until it breaks.
[0231] Peel strength: The standard is ASTM D903, the method is to bond stainless steel sheets (25×100 mm), peel at 180°, and the rate is 100 mm / min.
[0232] Water absorption rate: The method is to immerse the cured sample in 25℃ deionized water for 24 hours, weigh it and calculate the percentage of mass increase.
[0233] Thermal conductivity: The standard is ASTM E1530, the instrument is a thermal conductivity meter (HotDisk TPS2500S), and the sample thickness is 2 mm.
[0234] Solvent resistance: The method is to immerse the cured sample in acetone for 24 hours and observe the surface swelling, delamination or dissolution.
[0235] Curing time: The method is finger touch method (surface dry) + DSC verification of the end time of the exothermic peak of complete curing.
[0236] Table 1 Properties of water-based adhesives in Examples 1 to 3 and Comparative Examples 1 to 8
[0237]
[0238] As shown in Table 1, the tensile strength of the water-based adhesives of Examples 1 to 3 is 25.3 to 31.4 MPa, the elongation at break is 291% to 323%, the peel strength is 7.5 to 9.2 N / mm, the water absorption is 4.9% to 6.8%, the thermal conductivity is 0.38 to 0.52 W / m·K, and the curing time is 12.2 to 18.3 min.
[0239] Comparative Example 1 lacks N-(3,4-dihydroxyphenylethyl)methacrylamide, which deprives the catechol group of its metal chelation and wet hydrogen bonding capabilities. Peel strength plummets by 62%, and interfacial delamination leads to an 81% increase in water absorption.
[0240] In Comparative Example 2, the absence of phenylboronic acid-functionalized polyethylene glycol caused the dynamic borate ester bond to break, resulting in a loss of stress dispersion and self-healing capabilities. The elongation at break dropped 42%, and the curing time was extended by 87%.
[0241] In Comparative Example 3, the polyethyleneimine-dopamine copolymer was missing, causing the biomimetic adhesion function to fail (due to the lack of dopamine), and the substrate wettability collapsed. The peel strength dropped to a minimum of 2.9 N / mm (a 68% decrease), and the solvent resistance was completely lost.
[0242] In Comparative Example 4, the absence of sulfobetaine methacrylate (SBMA) caused the zwitterion's anti-hydration barrier to collapse, exacerbating solvent penetration. Water absorption surged by 168%, while tensile strength plummeted by 60%.
[0243] Comparative Example 5 lacks the epoxidized cardanol-polycaprolactone copolymer, causing the main resin to disappear, the continuous phase structure and the hydrophobic barrier to collapse. The tensile strength plummeted by 69%, the water absorption soared by 272%, and the sample disintegrated.
[0244] In Comparative Example 6, methyltetrahydrophthalic anhydride was missing, and the epoxy groups could not be ring-opened and cured, resulting in insufficient crosslinking density. The tensile strength decreased by 47%, and the solvent resistance was partially dissolved.
[0245] In Comparative Example 7, the sulfobetaine / boron nitride hybrid filler was missing, resulting in a disruption of the thermally conductive particle network and concentrated interfacial stress. The thermal conductivity dropped sharply by 53%, and the peel strength decreased by 30%.
[0246] In Comparative Example 8, the acrylic acid boric acid core-shell hyperbranched polyester was missing, resulting in a reduced crosslinking density, loss of network density and toughening effect, severe solvent swelling, and a 32% reduction in elongation at break.
[0247] The water-based adhesive obtained in the embodiment of the present application can be used in multiple fields, specifically:
[0248] (1) Electronic and electrical field: Since the adhesive of the embodiment has good thermal conductivity (thermal conductivity coefficient 0.38W / mK to 0.52W / mK), it can be used for heat dissipation packaging of electronic components, such as bonding between chips and heat sinks, which can effectively conduct heat away and prevent electronic components from being damaged by overheating. At the same time, its good mechanical properties and solvent resistance can also ensure the stability of electronic equipment during long-term use.
[0249] (2) Construction: In the construction industry, the adhesive can be used for bonding structural parts, such as connecting concrete components and pasting tiles to walls. Its high tensile strength and peel strength can ensure the firmness of the bonding parts, while its low water absorption rate can reduce the impact of moisture on the bonding performance and improve the durability of the building structure. In addition, its moderate curing time facilitates construction operations.
[0250] (3) Automobile manufacturing: During the automobile manufacturing process, a large amount of adhesives are required to bond various parts, such as body panels and interior trims. The mechanical properties of the adhesive in the embodiment can meet the bonding strength requirements of automobile parts. At the same time, its solvent resistance and weather resistance can ensure that it is not corroded by solvents such as fuel and lubricating oil during automobile use, and can resist the influence of the external environment.
[0251] (4) Aerospace: The aerospace field has very high requirements for material performance. The excellent mechanical properties and solvent resistance of the adhesive in the example give it certain application potential in the aerospace field. For example, it can be used for bonding aircraft structural parts and encapsulating satellite components, and can ensure reliability and stability in extreme environments.
[0252] (5) Packaging field: For some packaging materials that require high-strength sealing and bonding, such as composite packaging of metal foil and plastic film, the tensile strength and peel strength of the adhesive in the embodiment can meet the requirements. At the same time, its water resistance and solvent resistance can ensure the safety of the packaging contents during storage and transportation.
[0253] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a hard limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numbers within the range. For example, the description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0254] In addition, in the description of this application, the terms "including", "comprising", etc. mean "including but not limited to". In this document, relational terms such as "first" and "second" are merely used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations.
[0255] The foregoing is merely a list of specific embodiments of the present application, intended to enable those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application is not limited to the embodiments shown herein, but is intended to conform to the broadest scope consistent with the principles and novel features of the present application.
Claims
1. A water-based adhesive, characterized in that: The water-based adhesive is composed of the following chemical components, in parts by mass: 3.5 to 5.0 parts of N-(3,4-dihydroxyphenylethyl) methacrylamide, 2.5 to 3.5 parts of phenylboronic acid functionalized polyethylene glycol, 1.2 to 2.0 parts of polyethyleneimine-dopamine copolymer, 3.0 to 4.0 parts of sulfobetaine methacrylate, 27.0 to 32.0 parts of epoxidized cardanol-polycaprolactone copolymer, 7.0 to 10.0 parts of methyltetrahydrophthalic anhydride, 4.5 to 6.5 parts of sulfobetaine / boron nitride hybrid filler, 6.0 to 8.0 parts of acrylic acid boric acid core-shell hyperbranched polyester, 0.3 to 0.5 parts of photoinitiator, 0.3 to 0.5 parts of leveling agent, and 30.0 to 35.0 parts of deionized water.
2. The water-based adhesive according to claim 1, characterized in that The number average molecular weight of the phenylboronic acid functionalized polyethylene glycol is 1800 to 2200, and the phenylboronic acid grafting rate is 85 to 95%; and / or, In the polyethyleneimine-dopamine copolymer, the branching degree of polyethyleneimine is 0.35-0.45, and the grafting amount of dopamine is 1.8-2.2 mmol / g; and / or, The epoxy value of the epoxidized cardanol-polycaprolactone copolymer is 0.25-0.35 eq / 100 g, and the molecular weight of the polycaprolactone segment is 2000-3000.
3. The water-based adhesive according to claim 1, characterized in that The core of the acrylic acid boric acid core-shell hyperbranched polyester is a hyperbranched polyester, and the shell is acrylic acid boric acid. The generation number of the hyperbranched polyester is 3.0-4.0, and the functionality of the acrylic acid boric acid is 2.8-3.2 mmol / g.
4. The water-based adhesive according to claim 1, characterized in that In the sulfobetaine / boron nitride hybrid filler, the boron nitride is hexagonal boron nitride, and the sulfobetaine methacrylate is modified on the surface of the hexagonal boron nitride, with the modification amount being 20-25% of the mass of the hexagonal boron nitride.
5. The water-based adhesive according to claim 1, characterized in that The photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone; and / or The leveling agent is polyether modified siloxane.
6. A method for preparing the water-based adhesive according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: S1, mixing N-(3,4-dihydroxyphenylethyl) methacrylamide, phenylboronic acid functionalized polyethylene glycol, polyethyleneimine-dopamine copolymer, sulfobetaine methacrylate and deionized water, and adjusting the pH to 6.8-7.2 to obtain a first mixed solution; S2, adding a photoinitiator to the first mixed solution to perform ultraviolet light curing to obtain a second mixed solution; S3, plasma-treating the sulfobetaine / boron nitride hybrid filler to obtain a pretreated filler; S4, adding epoxidized cardanol-polycaprolactone copolymer, methyltetrahydrophthalic anhydride and acrylic acid boric acid core-shell hyperbranched polyester to the second mixed solution, then performing stepwise thermal curing, and adding pretreated filler during the stepwise thermal curing process to obtain a third mixed solution; S5. Add a leveling agent to the third mixed liquid cooled to room temperature to obtain a water-based adhesive.
7. The method for preparing the water-based adhesive according to claim 6, wherein: The wavelength of the UV curing is 365nm, the irradiation time is 5-10min, and the light intensity is 50-70mW / cm 2 and / or, The working gas for the plasma treatment is an argon / oxygen mixed gas with a volume ratio of 4:1, the power is 100 W, and the treatment time is 2 to 5 minutes.
8. The method for preparing the water-based adhesive according to claim 6, wherein: The S4 step includes: S401, adding epoxidized cardanol-polycaprolactone copolymer, methyltetrahydrophthalic anhydride and acrylic acid boric acid core-shell hyperbranched polyester to the second mixed solution to obtain a first epoxy mixture; S402, heating the first epoxy mixture to 70° C. and keeping the temperature for 2 hours to obtain a second epoxy mixture; S403, continuing to heat the second epoxy mixture from 70° C. to 90° C. and keeping the temperature for 1 hour, adding the pretreated filler during the 1 hour of keeping the temperature, to obtain a third epoxy mixture; S404, continuing to heat the third epoxy mixture from 90° C. to 120° C. and keeping the temperature for 30 minutes to obtain a third mixed solution.
9. The method for preparing the water-based adhesive according to claim 6, wherein: The preparation method of the sulfobetaine / boron nitride hybrid filler comprises: dispersing hexagonal boron nitride powder in concentrated nitric acid to perform surface hydroxylation on the hexagonal boron nitride to obtain activated hexagonal boron nitride; The activated hexagonal boron nitride is dispersed in deionized water, and then sulfobetaine methacrylate monomer and azobisisobutylamidine hydrochloride are added, and a graft polymerization reaction is carried out under nitrogen protection to covalently bond the sulfobetaine methacrylate to the surface of the hexagonal boron nitride to obtain the sulfobetaine / boron nitride hybrid filler; Wherein, the mass of the sulfobetaine methacrylate monomer is 20% to 25% of the mass of the hexagonal boron nitride; The mass of the azobisisobutylamidine hydrochloride is 1 to 2% of the mass of the sulfobetaine methacrylate monomer; The graft polymerization reaction temperature is 60-70° C. and the reaction time is 8-12 hours.
10. The method for preparing the water-based adhesive according to claim 6, wherein: The preparation method of the acrylic acid boric acid core-shell hyperbranched polyester comprises: Pentaerythritol, malonic anhydride and p-toluenesulfonic acid are dissolved in xylene solvent to carry out polycondensation reaction to obtain hyperbranched polyester; The hyperbranched polyester is dissolved in tetrahydrofuran, and then acrylic acid boronic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are added to introduce acrylic acid boronic acid groups into the terminal hydroxyl groups of the hyperbranched polyester to obtain the acrylic acid boronic acid core-shell hyperbranched polyester; Wherein, the molar ratio of the pentaerythritol to the malonic anhydride is 1:(3-4); The mass of the p-toluenesulfonic acid is 0.5 to 1.5% of the total mass of the pentaerythritol and the malonic anhydride; The polycondensation reaction temperature is 140-160°C and the time is 4-6 hours; The functionality of the acrylic acid boronic acid is 2.8 to 3.2 mmol / g, and the molar ratio of the acrylic acid boronic acid to the hydroxyl group of the hyperbranched polyester is (1 to 1.2):1; The molar ratio of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to the acrylic acid boric acid is (1.5-2.0):1; The thickness of the acrylic acid boric acid shell layer is 5 to 10 nm.